Reflexões sobre a forma de recrutamento das Forças Armadas Brasileiras e suas implicações para a defesa nacional - João Paulo Soares Alsina Jr (Universidade do Estado do Rio de Janeiro, 2010)
Military recruitment in Brazil is a "non-issue". Given the lack of research on the subject, the current article attempted to approach it in conceptual terms in order to back potential discussions in the future. The implications of the current draft system for the Brazilian Army were analyzed. Future demands on the Brazilian Armed Forces in relation to international security were outlined. Based on this potential scenario, the ideal military profile for the country was inferred. The study suggests changes in the recruitment system to allow the Army to adjust its current structure to the detected needs. The analysis indicates that the proposed reform can only be carried out through a decision emanating from the country's civilian leadership.